2013
DOI: 10.1093/rheumatology/ket349
|View full text |Cite
|
Sign up to set email alerts
|

Systemic involvement in primary Sjogren's syndrome evaluated by the EULAR-SS disease activity index: analysis of 921 Spanish patients (GEAS-SS Registry)

Abstract: Primary SS is undeniably a systemic disease, with the joints, lungs, skin and peripheral nerves being the most frequently involved organs. Cytopenias, hypocomplementaemia and cryoglobulinaemia at diagnosis strongly correlated with higher cumulated ESSDAI scores in the clinical domains. Clinically the ESSDAI provides a reliable picture of systemic involvement in primary SS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
2
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(130 citation statements)
references
References 34 publications
10
108
2
10
Order By: Relevance
“…Older patients at the time of diagnosis (> 70 years) were less active during follow-up, but had a higher pulmonary activity score. 7 Findings on the chest HRCT scan in our study were more common in patients with arthritis, but the group with these complications was relatively small.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Older patients at the time of diagnosis (> 70 years) were less active during follow-up, but had a higher pulmonary activity score. 7 Findings on the chest HRCT scan in our study were more common in patients with arthritis, but the group with these complications was relatively small.…”
Section: Discussionmentioning
confidence: 45%
“…It is suggested that a score of 5 points is associated with moderate pSS activity and > 14 points with shorter survival. 6,7 The aim of this study was to assess the incidence of pulmonary manifestations in pSS and to determine factors predisposing to this complication.…”
mentioning
confidence: 99%
“…The results displayed reliable thresholds for defining activity levels and changes in scores that could be used for designing future clinical trials. Nevertheless, since the number of observational cohorts already used ESSDAI and ESSPRI for the evaluation of their real-life patients,6 26 the usefulness of these thresholds in clinical practice will be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, renal involvement occurs in 4-5% of pSS patients (25)(26)(27). TIN is the predominant condition, found in 75% of patients, with the remaining 25% of patients having glomerular disease (28,29).…”
Section: N Renal Involvementmentioning
confidence: 99%